Factors influencing the success of ICT telecentre projects in rural communities in Malaysia - Bashir, Muhammad Sani (2011)
The aim of the study was to identify factors influencing the success of telecentre projects in rural communities in Malaysia. The study employed quantitative research methodology, using cross sectional survey design. A Stratified random sampling was used in selecting the respondents of the study. Four stages were followed in determining the sample of the study. (1) Dividing the study area into four zones (2) Selecting the states (3) Selecting the PIDs and (4) Selecting the respondents. The sample size of involved 138 respondents who were randomly selected from 11 Pusat Internet Desa (PIDs) from the four states involved in this study. Data were collected through selfadministered questionnaires. The Data was analyzed using SPSS software, version 17. The statistical analysis used were descriptive statistics, Pearson correlation and Spearman Rho correlation analyses and Stepwise multiple linear regression. The result of the Pearson-Moment correlation analyses revealed that there was significant positive relationship between the selected factors that is competency of leader, location, infrastructure, local/relevant content, computer skills, community participation, and community needs) and the success of telecentre projects. However, the result showed that there was no significant relationship between age of the respondents and the success of telecentre projects. Also the spearman Rho correlation analysis showed that there was no significant relationship between level of education and the success of telecentre projects. The Stepwise multiple linear regression unveiled that competency of leaders, infrastructures and community need are important factors that make the most significant contribution towards the success of telecentre projects in rural communities. Based on the findings of the analyses it can be concluded that competency of leader, suitable location, availability of appropriate infrastructures, providing quality of services, and locally relevant information, high level of computer skills, community participation and meeting community needs lead to the success of telecentre projects in rural communities. Based on the stepwise multiple linear regression analysis, competency of leaders made the highest contribution, explained 53.8% of variance in the success of telecentre projects followed by infrastructures which explained additional 8.2% and then community needs which explained additional 2.8% of variance in the success of telecentre projects. Therefore special consideration should be given to all factors and efforts should always be made to improve upon them in the following ways: by engaging competent leaders who are well qualified to manage the centers, locating the centres in suitable location, equipping the centers with required facilities and regularly updating them; providing locally and relevant contents in local language, improving the computer skills of the respondents, enhancing community participation and finally by providing services that respond to the needs and aspirations of members of the community for which such projects are targeted at.